Update on RAAS Modulation for the Treatment of Diabetic Cardiovascular Disease. (29th August 2016) - Bernardi, Stella; Michelli, Andrea; Zuolo, Giulia; Candido, Riccardo; Fabris, Bruno
Abstract : Since the advent of insulin, the improvements in diabetes detection and the therapies to treat hyperglycemia have reduced the mortality of acute metabolic emergencies, such that today chronic complications are the major cause of morbidity and mortality among diabetic patients. More than half of the mortality that is seen in the diabetic population can be ascribed to cardiovascular disease (CVD), which includes not only myocardial infarction due to premature atherosclerosis but also diabetic cardiomyopathy. The importance of renin-angiotensin-aldosterone system (RAAS) antagonism in the prevention of diabetic CVD has demonstrated the key role that the RAAS plays in diabetic CVD onset and development. Today, ACE inhibitors and angiotensin II receptor blockers represent the first line therapy for primary and secondary CVD prevention in patients with diabetes. Recent research has uncovered new dimensions of the RAAS and, therefore, new potential therapeutic targets against diabetic CVD. Here we describe the timeline of paradigm shifts in RAAS understanding, how diabetes modifies the RAAS, and what new parts of the RAAS pathway could be targeted in order to achieve RAAS modulation against diabetic CVD.